Cassius Dio's Speeches and the Collapse of the Roman Republic : The Roman History, Books 3-56 - Burden-Strevens, Christopher (Historiography of Rome and Its Empire Ser, 2020)
Intro -- Contents -- Historiography of Rome and Its Empire Series -- Acknowledgements -- Table of Speeches -- Chapter 1 Introduction -- 1 From One King to Another -- 2 Speechwriting and the Historian -- 3 Cassius Dio and the Decline of the Republic -- 4 The Historian and his World -- 5 Using This Book -- Chapter 2 Method -- 1 The Composition of Dio's Speeches: Three Problems -- 1.1 Narrative and Dramatic Setting -- 1.2 Sources and Models -- 1.3 Rhetorical Education and Moralising Argument -- 2 Three Problems, or Three Strengths? -- Chapter 3 Oratory -- 1 Beginnings: Early Roman Oratory -- 2 Decline: Dynasty and Deception -- 3 Restoration: Augustus and the Principate -- Chapter 4 Morality -- 1 Envy and Odium -- 2 Selfish Ambition, or Love of Honour? -- 3 Covetousness and Cupidity -- 4 Moral Revolution, or Constitutional Change? -- Chapter 5 Institutions &amp -- Empire -- 1 Successive Office-Holding and the High Command -- 2 The Dictatorship and Tyranny -- 3 Tradition and Innovation -- Chapter 6 Epilogue -- Bibliography -- Index.